ANALISA TINGKAT BAHAYA EROSI DALAM RANGKA PERENCANAAN REHABILITASI DAN KONSERVASI TANAH AREAL MODEL MIKRO DAS (MDM) MARAWAS SWP DAS TONDANO - Noldy R. Kumendong; Hengki D. Walangitan; Johny S. Tasirin; Alfonsius Thomas (Universitas Sam Ratulangi, 2015)
ABSTRACT Marawas is one of the most important watershed in Tondano watershed in Minahasa. The erosion that happens at Marawas watershed caused by land change and human activity. This study helps us to analyze the erosion risk levels in Marawas watershed. Field survey was to document land cover, slope length, slope depth. The erosion risk Level were determined by USLE (R,K,L,S,CP). The study shows that the erosion risk levels of Marawas watershed are very light (62.5924 ha, 51,09%), light (0.7397 ha, 0,6%), middle (0.7397 ha, 0,6%), heavy (0 ha 0%) and very heavy (0,2792 ha, 0,23%). Marawas watershed hasthe average of erosion’s rate of 49.45 tonnes/ha/year or light level of Light erosion risk.